Socialist People's Libyan Arab Jamahiriya : A Public Expenditure Review, Volume 1. Synthesis - World Bank (Washington, DC, 2013)
Libya's 2008-12 development programs is the biggest and most ambitious Public Investment Program (PIP) ever. Public expenditure has also been pro-poor. Past outcomes show that Libyan authorities have worked on their macroeconomic and social fundamentals, so as to have a solid base to sustain its steady progress toward building a market-based economy and reintegrating into the world economy. Making optimal use of a sizable public expenditure, and especially public investment, is an essential component of achieving this strategy. The reports built upon the framework of fiscal management in oil-dependent economies, which features three parts. The first deals with collecting and saving oil revenues, leading to one stream of a large literature exploring both fiscal sustainability and the pros and cons of alternative models of an oil stabilization fund. The second deals with development spending, leading to a second stream of a large literature assessing standards in public investment and the many effects of sizable public investment programs. The third deals with financing current spending, such as wages, subsidies, or social programs, addressing the ongoing civil service reform and the Wealth Distribution Program (WDP).